Synthesis of Nano-Sized Yag:Ce3+ by Sol- Gel Method - Loli Yusastri; I. M. Joni; C. Panatarani (IPTEK The Journal for Technology and Science, 2008)
We have been successfully synthesized YAG- :Ce3+ nanoparticle (60 nm in sized) having high crystalinity by using low temperature sol gel method. Due to additional of polyethylene glycol into the precursor source has been avoid inter particle hard-agglomeration. The influence of difference heating process on the crystallinity of YAG:Ce3+ was studied by means of XRD characterization. The highest crystallinity of YAG:Ce3+ was achieved via two step heating at 900 and 1100oC.